DETERMINATION OF SOME TOXIC TRACE ELEMENTS OF FRESH, FROZEN AND CANNED FISH SPECIES - Munir Abood Jasim AL-Taee; Abdulkareem Taher Yesser (Basrah Journal of Veterinary Research)
In this study, fresh fish (Otolithes ruber, Saurida tumbil, Pseudorhombus malayanus, Acanthopagrus latus, Hypophthalmichthys molitrix and Tenualosa ilisha), imported frozen fish (Megalaspis cordyla, Ctenopharyngodon idella, Labeo rohita and Acanthopagrus latus) and imported canned fish species (sardines, mackerel and tuna) were used to detect and determine some toxic trace elements. All fish samples contained trace elements. The total concentrations mean for Cu, Zn, Pb, Ni, Co, Cd and Mn were between (1.73-11.93), (8.75-25.80), (ND-3.19), (0.11-0.31), (0.10-0.35), (0.23-3.00) and (0.11-1.86) mg/kg dry weight respectively in muscles of fresh fish, and between (13.21-53.74), (6.61-43.93), (0.35-2.10), (0.37-2.30), (0.20-0.54), (1.50-3.53) and (0.13-4.50)mg/kg dry weight respectively in the muscles of frozen fish species, and between(21.75-56.30), (5.21-82.84), (0.25-1.51), (0.33-1.96), (0.20-0.47), (0.51-2.22) and (0.13-0.81) mg/kg dry weight respectively in canned fish . Concentrations average of some trace elements were exceeded the permitted legal limits that set by the Food and Agriculture Organization and the World Health Organization.